The Teaching of Report Text by Using Instagram to The Tenth Graders - Fauzia, Yona; Febrianti, Yusnita; Tresnadewi, Sintha (Universitas Negeri Malang, 2024)
Writing is one of the fundamental English skills that students must master, yet it is also one of the most challenging. Students often struggle to express their ideas in written form and are unsure of what to write. To write effectively, students need a clear idea or inspiration, and one way to generate ideas is through pictures. Pictures can help center students' attention on the content, providing visual stimuli that inspire imagination and creativity. Specifically, pictures on Instagram can serve as valuable tools for students, allowing them to focus their attention and build their ideas. This research explores the use of Instagram as a tool for teaching report text writing in senior high school. The subjects were tenth-grade students of SMAN 4 Malang. The researcher employed a descriptive qualitative method, documenting the teaching and learning process and gathering students' responses through questionnaires. The results indicated that teaching report text writing using Instagram involved six steps: introducing the concept and purpose of report text writing, selecting appropriate pictures on Instagram, discussing and analyzing the pictures to generate ideas, guiding students in organizing their ideas, having students write their report texts, and reviewing and providing feedback. An impressive 85.7 percent of students agreed that Instagram should be used as a tool for learning writing. This structured approach made the writing process more engaging and interactive, significantly enhancing students' ability to generate and organize ideas, ultimately improving their writing skills. The positive response from the majority of students highlights the effectiveness and potential of using social media platforms like Instagram as innovative tools in educational settings.